1962
DOI: 10.2105/ajph.52.10.1697
|View full text |Cite
|
Sign up to set email alerts
|

Death Rates Among Physically Active and Sedentary Employees of the Railroad Industry

Abstract: Studies have indicated that men in sedentary occupations are more liable to have coronary heart disease than those in occupations requiring moderate to heavy physical activity. To test this hypothesis a study was conducted of the death rates among clerks, switchmen, and section men employed in the railroad industry. MORRIS, et al.,1 demonstrated an association between the physical activity required by an occupation and the incidence of coronary heart disease over a period of two years among bus drivers and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1
5

Year Published

1965
1965
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(54 citation statements)
references
References 10 publications
3
43
1
5
Order By: Relevance
“…Such a ratio is in line with those reported by similar studies on large cohorts, like the relative risk of 1.3-1.6 found in a survey of American railroad men (22) and the value of 1.7-1.8 for Californian longshoremen (16). In our group this ratio was substantially similar in the five-and ten-year follow-up (1.65 and 1.7, respectively), a finding suggesting that ageing and the increasing proportion of retirements do not decrease the protection of physical activity against fatal CHD in the form of MI or SD.…”
Section: Commentssupporting
confidence: 92%
See 1 more Smart Citation
“…Such a ratio is in line with those reported by similar studies on large cohorts, like the relative risk of 1.3-1.6 found in a survey of American railroad men (22) and the value of 1.7-1.8 for Californian longshoremen (16). In our group this ratio was substantially similar in the five-and ten-year follow-up (1.65 and 1.7, respectively), a finding suggesting that ageing and the increasing proportion of retirements do not decrease the protection of physical activity against fatal CHD in the form of MI or SD.…”
Section: Commentssupporting
confidence: 92%
“…The role of physical activity as a coronary risk factor has been debated for a long time, and opinions have contrasted due to the difficulties of classifying single individuals as more or less active and to the confounding effects between habitual physical activity and some other risk factors, which, at least in some extensive surveys, could not be measured (1,2,3,4,6,7,8,9,10,11,12,13,14,15,16,17,18,19,21,22,24 0355-3140/79/020100-9…”
mentioning
confidence: 99%
“…Many studies have documented an inverse association between job-related PA and overall CHD risk. Among these studies, Taylor et al 8 evaluated PA and CHD risk in over 190,000 US railroad workers and showed that death caused by atherosclerosis was more frequent in the relatively sedentary clerks (relative risk, 2.0) and moderately active switchmen (relative risk, 1.5) than in the section men who had high PA. Morris et al 9 studied PA in 667 male London bus drivers and conductors and determined that CHD was much lower for the more active conductors than for the drivers (age-adjusted relative risk, 1.8 risk, 1.8 for light PA and 1.7 for moderate PA vs heavy PA). However, these studies are now principally of historical interest because few jobs today require the level of PA described in these studies.…”
Section: Observational Studies and Primary Chd Preventionmentioning
confidence: 99%
“…Research in the 1950s and 1960s, comparing different occupational groups, identified sedentary work as an important cardiovascular risk factor (76)(77)(78)(79). However, these earlier studies were vulnerable to alternative explanations because of selection bias and uncontrolled confounding.…”
Section: Comparison With Other Studies and Known Risk Factorsmentioning
confidence: 99%